Deep Breathing Relaxation Exercises To Decrease The Scale Of Pain in Mothers Post Sectio Caesarea (HEALTH CARE: JURNAL KESEHATAN, 2024)
The problem with postoperative section caesarean (SC) patients that often arises is pain. Pain is especially felt on the first and second day, so the patient needs help fulfilling their daily needs. This study aims to determine the effect of deep breathing relaxation on post sc patient pain. The research was carried out at Ryacudu Hospital in July-October 2018. The research design was a quasy experiment with a pre-post test design with a control group. The research sample was 78 respondents who were divided into two, namely the intervention group and the control group. The independent variables studied were deep breathing relaxation as the independent variable and pain as the dependent variable. The analysis used is the independent t test. The results of the study, 70.5% of respondents aged 20-35 years, 55.1% secondary education, 66.7% first parity, and 73.1% first surgery experience. There was a decrease in the average pain score in the intervention group from 6.23 to 3.41 and in the control group from 5.64 to 4.59. The result is that there is a significant effect of deep breathing relaxation exercises on reducing the pain scale of postoperative SC patients, p = 0.000. Provision of deep breathing relaxation is very appropriate for postoperative SC patients